Antioxidant responses of Propylaea japonica (Coleoptera: Coccinellidae) exposed to high temperature stress. (February 2015) - Zhang, Shize; Fu, Wenyan; Li, Ning; Zhang, Fan; Liu, Tong-Xian
Graphical abstract: Highlights: Effects of high temperature stress on Propylaea japonica were examined. P. japonica adults could not survive at 43 °C. Catalase, glutathione-S-transferases and total antioxidant capacity were increased. Superoxide dismutase and peroxidases were increased when temperature was above 37 °C. Malondialdehyde concentrations were increased when temperature was above 37 °C. Abstract: Temperature is one of the most important environmental factors, and is responsible for a variety of physiological stress responses in organisms. Induced thermal stress is associated with elevated reactive oxygen species (ROS) generation leading to oxidative damage. The ladybeetle, Propylaea japonica (Thunberg) (Coleoptera: Coccinellidae), is considered a successful natural enemy because of its tolerance to high temperatures in arid and semi-arid areas in China. In this study, we investigated the effect of high temperatures (35, 37, 39, 41 and 43 °C) on the survival and activities of antioxidant enzymes, including superoxide dismutase (SOD), catalase (CAT), peroxidases (POD), glutathione-S-transferases (GST), and total antioxidant capacity (TAC) as well as malondialdehyde (MDA) concentrations in P. japonica adults. The results indicated that P. japonica adults could not survive at 43 °C. CAT, GST and TAC were significantly increased when compared to the control (25 °C), and this played an important role in the process of antioxidant response to thermal stress. SOD and POD activity, as well as MDA, did not differ significantly at 35 and 37 °C compared to the control; however, there were increased levels of SOD, POD and MDA when the temperature was above 37 °C. These results suggest that thermal stress leads to oxidative stress and antioxidant enzymes play important roles in reducing oxidative damage in P. japonica adults. This study represents the first comprehensive report on the antioxidant defense system in predaceous coccinellids (the third trophic level). The findings provide useful information for predicting population dynamics and understanding the potential for P. japonica as a natural enemy to control pest insects under varied environmental conditions.